2008
DOI: 10.1016/j.freeradbiomed.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency activates mouse liver Nrf2–ARE but vitamin E deficiency does not

Abstract: Selenium (Se) and vitamin E are antioxidant micronutrients. Se functions through selenoproteins and vitamin E reacts with oxidizing molecules in membranes. The relationship of these micronutrients with the Nrf2-antioxidant response element (ARE) pathway was investigated using ARE-reporter mice and Nrf2-/- mice. Weanling males were fed Se-deficient (0 Se), vitamin E-deficient (0 E), or control diet for 16 or 22 weeks. The ARE reporter was elevated 450-fold in 0 Se liver but was not elevated in 0 E liver. Antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 37 publications
(44 reference statements)
3
53
2
Order By: Relevance
“…36). A link between NRF2 and selenium metabolism has been characterized, but this depended on the tissue analyzed (51,52). In HEK293 cells, we observed very little regulation of selenoprotein mRNA levels as a function of selenium bioavailability or oxidative stress, even though selenoprotein expression was modulated dramatically, indicating a specific translational control of this family of proteins in the cell line analyzed.…”
Section: Discussionmentioning
confidence: 72%
“…36). A link between NRF2 and selenium metabolism has been characterized, but this depended on the tissue analyzed (51,52). In HEK293 cells, we observed very little regulation of selenoprotein mRNA levels as a function of selenium bioavailability or oxidative stress, even though selenoprotein expression was modulated dramatically, indicating a specific translational control of this family of proteins in the cell line analyzed.…”
Section: Discussionmentioning
confidence: 72%
“…A simultaneous disruption of Trsp and Nrf2 abolished the induction of phase II enzymes, thus, verifying the role of Nrf2 in responding to the loss of selenoproteins [52]. The ARE-driven reporter gene activity in ARE-reporter mice fed a selenium-deficient diet was strongly enhanced compared to mice fed the control diet [9]. In addition, the increased GST and NQO1 activity observed in selenium-deficient wild type mice was not detectable in Nrf2 -/-mice [9].…”
Section: Introductionmentioning
confidence: 72%
“…The establishment of a marginal selenium-deficiency is in contrast to most of the other studies investigating the effects of either high selenium supplementation or severe selenium-deficiency. Also Burk and colleagues, who provided the first direct link between dietary selenium-deficiency and Nrf2 activation, compared mice fed either a completely seleniumdeficient or a -supplemented diet with 0.25 mg sodium selenite per kg [9]. Under selenium-deficient conditions, ARE-driven reporter gene activity as well as GST and NQO1 activity were strongly increased in the liver of wild-type mice but were unchanged in Nrf2 -/-mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that selenium deficiency causes oxidative conditions in the liver, thus leading to activation of transcriptional factor AP-1-mediated induction of such stress responsive enzymes. With respect to selenium-deficient animals, Burk et al (2008) found the increase in Nrf2/ARE system and its regulatory enzymes of NQO1, HO-1 and GST. However, such an increase in the antioxidant responsive system did not occur with vitamin E deficiency.…”
Section: Pb As An Inducer Of Ho-1 In Selenium-deficient Animalsmentioning
confidence: 94%